Cancer Risk in Inflammatory Bowel Disease - Anders M Ekbom (Canadian Journal of Gastroenterology)
There is an increased risk of cancer in both ulcerative colitis and Crohn's disease. In 3121 patients with ulcerative colitis, 225 cases of cancer were diagnosed compared with 142.1 expected (standardized incidence ratio [SIR] 1.6, 95% CI 1.4 to 1.8), and in 1655 patients with Crohn's disease, 58 cases of cancer were detected compared with 47.1 expected (SIR 1.2, 95% CI 0.9 to 1.6). After excluding colorectal cancer the observed number of malignancies was very close to that expected for ulcerative colitis (SIR 1.0, 95% CI 0.9 to 1.2) and for Crohn's disease (SIR 1.1, 95% CI 0.8 to 1.5). Thus, the increased risk of cancer in inflammatory bowel disease is confined to colorectal cancer. In Crohn's disease 12 cases of colorectal cancer were observed (SIR 2.5, 95% CI 1.3 to 4.3). The increased risk was confined to those with colonic involvement and young age at diagnosis. In patients with colonic involvement and younger than age 30 years at diagnosis, the SIR was 20.9 (95% CI 6.8 to 48.7) versus 2.2 for those older than 30 years at diagnosis (95% CI 0.6 to 5.7). In ulcerative colitis 91 cases of colorectal cancer were observed with an SIR of 5.7 (95% CI 4.6 to 7.0). Extensive disease and young age at diagnosis were independent risk factors. Pancolitis at diagnosis resulted in an SIR of 14.8 (95% CI 11.4 to 18.9), 2.8 in left-sided colitis (95% CI 1.6 to 4.4) and 1.7 in proctitis (95% CI 0.8 to 3.2). There is great variation in the risk estimates in different studies worldwide. Different treatment strategies could be an explanation, a hypothesis that was substantiated in a study of 102 cases of colorectal cancer among patients with ulcerative colitis compared with 196 controls. Pharmacological therapy with sulfasalazine entailed a strong protective effect against colorectal cancer (relative risk of 0.34, 95% CI 0.190 to 0.62).